KERJASAMA INDONESIA DAN CHILDFUND INTERNATIONAL DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI NUSA TENGGARA TIMUR PERIODE 2016-2019 - Saskia Aisy Anindya, (2021)
Education is a determinant factor on achieving of the quality of human resources in a country. As a developing country, Indonesia still has many challenges and obstacles in improving the quality of education evenly, especially in disadvantaged areas in Indonesia such as East Nusa Tenggara. East Nusa Tenggara still has a low quality of education, arranging from facilities for learning activities to the quality of the teachers. Therefore, Indonesia together with ChildFund International held a collaboration in order to improve the quality of education in East Nusa Tenggara. Through this collaboration, the Indonesian government together with ChildFund International and LPMM Kupang as ChildFund's local partners in Indonesia implemented several programs, such as Ropnoni Education Support Project and Gebyar Cerdas Anak dan Orang Tua. In these programs, the construction of a new building for an elementary school in East Nusa Tenggara was carried out as well as interactive activities for children and their parents, and a series of trainings for local teachers and supervisors.